Chip carving with Wayne Barton - Barton, Wayne; Barton, Wayne; Taunton Press (Newton, Conn. : Taunton Press, 1986)
Wayne Barton shows you how, demonstrating and explaining the simple tools and precise techniques involved in the work.
Keywords: Cabinetwork; Wood-carving.; Wood-carving -- Technique